2000
DOI: 10.1081/ada-100101898
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Social-Cognitive Model of Intimate Abusiveness Among Substance-Dependent Males

Abstract: Throughout history, the human race has been characterized by the use of physical and emotional aggression by individuals, particularly males, in their intimate relationships. Intimate abusiveness is particularly common among substance dependent males. As a result of male intimate abusiveness, victims suffer a variety of problems ranging from emotional trauma to death due to physical injury. Despite increased attention to this problem, our understanding of the process leading to intimate abusiveness is far from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
1
4
0
1
Order By: Relevance
“…Comparisons were made between men with and without a history of IPV. Consistent with previous research, the IPV group reported (explicitly) less relationship satisfaction (Stith, Green, Smith, & Ward, 2008) in addition to higher levels of relationship dominance and controlling behaviors (e.g., Graham-Kevan & Archer, 2009; Stets & Burke, 2005), hostility toward the opposite gender (e.g., Copenhaver, 2000; Holtzworth-Munroe & Hutchinson, 1993), instrumental beliefs about physical aggression (Próspero, 2008), stereotypical views of gender roles (e.g., Saunders, 1992; Stith & Farley, 1993), condoning attitudes toward physical IPV (e.g., Hanson, Cadsky, Harris, & Lalonde, 1997; Holtzworth-Munroe, Meehan, Herron, Rehman, & Stuart, 2000), and psychological entitlement (e.g., Rothschild, Dimson, Storaasli, & Clapp, 1997; Simmons, Lehmann, Cobb, & Fowler, 2005). These group differences remained significant after controlling for social desirability and relationship satisfaction suggesting that participants were generally honest in their responses and that any negative thinking patterns in relation to intimate relationships and intimate partners in this sample were not due to unhappiness with their relationship.…”
Section: Discussionsupporting
confidence: 87%
“…Comparisons were made between men with and without a history of IPV. Consistent with previous research, the IPV group reported (explicitly) less relationship satisfaction (Stith, Green, Smith, & Ward, 2008) in addition to higher levels of relationship dominance and controlling behaviors (e.g., Graham-Kevan & Archer, 2009; Stets & Burke, 2005), hostility toward the opposite gender (e.g., Copenhaver, 2000; Holtzworth-Munroe & Hutchinson, 1993), instrumental beliefs about physical aggression (Próspero, 2008), stereotypical views of gender roles (e.g., Saunders, 1992; Stith & Farley, 1993), condoning attitudes toward physical IPV (e.g., Hanson, Cadsky, Harris, & Lalonde, 1997; Holtzworth-Munroe, Meehan, Herron, Rehman, & Stuart, 2000), and psychological entitlement (e.g., Rothschild, Dimson, Storaasli, & Clapp, 1997; Simmons, Lehmann, Cobb, & Fowler, 2005). These group differences remained significant after controlling for social desirability and relationship satisfaction suggesting that participants were generally honest in their responses and that any negative thinking patterns in relation to intimate relationships and intimate partners in this sample were not due to unhappiness with their relationship.…”
Section: Discussionsupporting
confidence: 87%
“…Further, a number of studies have found that aggressive individuals have poor coping skills and cognitive styles conducive to aggression. Copenhaver (2000) found that men in SUD treatment with violence problems had less competent coping skills with regard to marital situations, as well as greater attribution of negative intent to their partner, and Lee et al (1997) found violent cocaine dependent men had greater difficulty with relaxation skills. Holtzworth-Munroe and Anglin (1991) found that violent men had less competent coping responses to certain marital situations (rejection, jealousy, challenges from partner) compared to distressed and non-distressed non-violent men.…”
Section: Introductionmentioning
confidence: 99%
“…The program included these components because of their link to domestic violence perpetration. In the literature, lower drug and alcohol use is associated with less domestic violence (Copenhaver, 1998;Gondolf and Foster, 1991;Hamberger and Hastings, 1991;Kantor and Straus, 1990). Interestingly, two statistically significant differences were observed in batterer self-reported alcohol and marijuana use.…”
Section: Discussionmentioning
confidence: 92%